Roepke Lecture in Economic Geography—Financial Literacy in Context. (January 2014) - Clark, Gordon L.
Abstract Financial literacy has caught the attention of policy makers around the world. A major research program has been initiated by the World Bank aimed at mapping patterns of financial literacy in developed and developing economies. In this article, I explain the conceptual foundations of the literacy project, develop a critique of its testing procedures, and suggest that, at the limit, it is an impossible project. At every turn, standard tests of financial literacy dissolve into spatially and temporally specific phenomena that undercut the possibility of shared interpretations of notionally common problems. Nonetheless, the literacy mapping project is important for what it reveals about the geographic and sociodemographic patterns of financial knowledge. My research on financial decision making has been based, in part, on a concern for the nature and scope of financial knowledge and understanding in the context of risk and uncertainty. Thus, the trick is to anchor financial literacy programs in ways that are relevant to everyday life. These arguments are illustrated with reference to the relevant literature, published and unpublished research on financial literacy among German residents, and an innovative financial literacy program that is fine‐tuned to people's circumstances.